2021
DOI: 10.3389/fpls.2021.642955
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Mapping Identified Quantitative Trait Loci for Grain Protein Concentration Expressing Independently of Grain Yield in Canadian Durum Wheat

Abstract: Grain protein concentration (GPC) is an important trait in durum cultivar development as a major determinant of the nutritional value of grain and end-use product quality. However, it is challenging to simultaneously select both GPC and grain yield (GY) due to the negative correlation between them. To characterize quantitative trait loci (QTL) for GPC and understand the genetic relationship between GPC and GY in Canadian durum wheat, we performed both traditional and conditional QTL mapping using a doubled hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The obtained high heritability and the moderate correlations observed among growing seasons demonstrated consistency of GPC across the environments and suggested a substantial genetic component to the variation of GPC. Comparable heritability estimates were also reported in previous studies [ 14 , 33 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The obtained high heritability and the moderate correlations observed among growing seasons demonstrated consistency of GPC across the environments and suggested a substantial genetic component to the variation of GPC. Comparable heritability estimates were also reported in previous studies [ 14 , 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies focused on durum wheat to explore the genetic factors of GPC. For instance, on the basis of a doubled haploid Canadian durum wheat population consisting of 162 lines derived from Pelissier × Strongfield cross and 1212 polymorphic single nucleotide polymorphisms (SNPs), four QTL ( QGpc.spa-2B.1 , QGpc.spa-2B.2 , QGpc.spa-3A.3 , and QGpc.spa-7A ) have been consistently detected in multiple environments [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional breeding techniques have been used to improve the GPC, but the expected rate of improvement has not been reached because of the strong environmental influence, the lack of a positive relationship betwixt grain yield and GPC, and the quantitative nature of the trait and low heritability ( Balyan et al, 2013 ). With the introduction of molecular markers and next-generation sequencing, as well as other biotechnological interventions, multiple genomic regions (genes/QTLs) linked to GPC have been discovered in wheat using several mapping populations ( Prasad et al, 2003 ; Zhao et al, 2010 ; Wang et al, 2012 ; Kumar et al, 2018 ; Ruan et al, 2021 ). Furthermore, it has been noted in several studies that QTLs found in one population may not be useful for improving traits in a different mapping population.…”
Section: Discussionmentioning
confidence: 99%
“…high quality wheat genome sequence and comparative genomics analysis with model species has speed up the genetic dissection of GPC in wheat cultivars ( Saini et al, 2020 ; Gill et al, 2022 ). Several GPC-QTLs have been reported and located across all the chromosomes of both common wheat (e.g., Boehm et al, 2017 ; Krishnappa et al, 2017 ; Cook et al, 2018 ; Su et al, 2020 ; Jiang et al, 2021 ) and tetraploid wheat ( Conti et al, 2011 ; Blanco et al, 2012 ; Marcotuli et al, 2017 ; Fatiukha et al, 2020 ; Ruan et al, 2021 ). However, very few reported QTLs could be successfully employed in molecular breeding programs mainly owing to the large confidence intervals (CIs), small phenotypic variation explained (PVE) by individual QTLs, and discrepancies in mapping results due to variations in the genetic backgrounds and environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving quality traits has long been an important goal in wheat breeding (Deng et al., 2013; Jin et al., 2016; Nelson et al., 2006). Due to the importance of protein and gluten content, test weight (TW) for bread production, nutritional value, and economic impact of end product quality, wheat quality breeding has also mainly focused on improving these essential components (Liu et al., 2017; Ruan et al., 2021; Sun et al., 2009).…”
Section: Introductionmentioning
confidence: 99%